Shaping the future : a dynamic process for creating and achieving your company's strategic vision - Belgard, William; Rayner, Steven R. (New York : AMACOM, 2004)
Provides how-to guidance - as well as examples based on interviews with executives from companies on how readers can help to create a future of their own choosing. Rethinking many classic assumptions about change, it emphasizes the importance of making a single, critical change - the strategic imperative - rather than many smaller ones. The book presents a practical and unique Transformational Model, consisting of five key steps necessary to overcome resistance and effect critical change within an organization.
Includes bibliographical references and index.
oif 12/03/15
Loan
Keywords: Strategic planning; Leadership; Industrial management; Organizational change